Penerapan Teknik Assertive Training Bagi ABK Tunagrahita di SKH Aditya Silih Asih - Dabur, Klaudia Sartika; Riyani, Setia; Dewi, Tyas Nurmaya; Muawanah, Muawanah; Amiro, Tri; Asdar, Ahsanul Khair (PERFECT EDUCATION FAIRY, 2025)
This dedication is motivated by the existence of less assertive behaviour in children with mental disability, so that children with special needs (ABK) with mental disability need special guidance so that they can behave more assertively through self-care independence programs. The purpose of this service is to find out the effectiveness of applying assertive training techniques to mentally retarded ABK at SKH Aditiya Silih Asih, Tangerang Regency. This program is assigned to 4 mild mentally retarded crew members run by the PKM-Community Service Team in collaboration with SKH educator Aditya Silih Asih and parents with ABK with mental retardation. Based on the results of observations and interviews, ABK has low behavioral control, tends to be annoying, and difficult to advise. In addition, at SKH Aditiya Silih Asih there are still no educators with a background in Guidance and Counseling, and there are only three educators with special educational backgrounds, so that the provision of treatment for ABK is still not entirely appropriate. The method used to achieve program success is by observing, interviewing, and questionnaires. The results obtained from filling out the questionnaire were 91%, which is high. This can be seen from the enthusiasm of ABK in participating in the program, as well as parents and educators, when participating in Sharing Session activities.